ANTESEDEN KEBERLANJUTAN BISNIS KELUARGA DI KAMPUNG BATIK LAWEYAN DAN KAUMAN SURAKARTA - Ari Susanti Utomo Wibisono (JURNAL LENTERA BISNIS, 2018)
AbstractThis study aims to find out about the sustainability of the family business in the villages of Batik Laweyan and Kauman. The success of a family-owned business succession has been revealed to be a very important phenomenon in the sustainability of the family business. This fact documents the importance of large family and investment businesses that have a family business. For good economic and family interests, it is important to determine predictors of family business sustainability. So this study will examine the factors that influence the involvement of future generations in the sustainability of family business. The total sample of 60 respondents is 30 respondents in Batik Laweyan Village and 30 respondents in Kauman Batik Village. The analysis used in this study is SPSS 21 with multiple linear analysis. The results of the research show that Entrepreneurial Thinking has a positive and significant effect, Entrepreneurial Knowledge Sharing has no effect and significant Family Business Sustainability. Successor Experience has a significant positive effect on Family Business Sustainability. Intergeneration conflict solution has a positive and significant effect on Family Business Sustainability. Keywords: Entrepreneurial Thinking, Entrepreneurial Knowledge Sharing, Successor Experiences, Intergeneration Conflict Solution.